The Effect of the Covid-19 Pandemic and the Economic Sector on Regional Tax Receiving in Cereal Farmers at Village - A’mal Bariq Imamuddin; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2023)
The Effect of the Covid 19 Pandemic and the Economic Sector on Regional Tax Revenue (Study on seleria farming in Payaman Village, Solokuro District, Lamongan Regency. This study was intended to determine the effect of the COVID-19 pandemic and the economic sector on local tax revenues (Study on seleria farming in Payaman Village, Solokuro District, Lamongan Regency.The purpose of this study is to find out how aware the public is in reporting and being able to pay taxes during an economic pandemic that causes a decline in economic activity This research is located in Payaman Solokuro Village, Lamongan with a sample size of 85 farmers. The type of research used is a type of quantitative research using statistical analysis and Statistical Product and Service Solution (SPSS). on selerian payaman solokuro lamongan farm)